Simultaneous Determination of Benzene and Toluene in Pesticide Emulsifiable Concentrate by Headspace GC-MS - Lidong Cao; Hua Jiang; Jing Yang; Li Fan; Fengmin Li; Qiliang Huang (Journal of Analytical Methods in Chemistry)
The toxic inert ingredients in pesticide formulations are strictly regulated in many countries. In this paper, a simple and efficient headspace-gas chromatography-mass spectrometry (HSGC-MS) method using fluorobenzene as an internal standard (IS) for rapid simultaneous determination of benzene and toluene in pesticide emulsifiable concentrate (EC) was established. The headspace and GC-MS conditions were investigated and developed. A nonpolar fused silica Rtx-5 capillary column (30 m×0.20 mm i.d. and 0.25 μm film thickness) with temperature programming was used. Under optimized headspace conditions, equilibration temperature of 120°C, equilibration time of 5 min, and sample size of 50 μL, the regression of the peak area ratios of benzene and toluene to IS on the concentrations of analytes fitted a linear relationship well at the concentration levels ranging from 3.2 g/L to 16.0 g/L. Standard additions of benzene and toluene to blank different matrix solutions 1ead to recoveries of 100.1%–109.5% with a relative standard deviation (RSD) of 0.3%–8.1%. The method presented here stands out as simple and easily applicable, which provides a way for the determination of toxic volatile adjuvant in liquid pesticide formulations.